Parathyroidectomy Positively Modulates Systemic Inflammation and Nutritional Status: Immune-Inflammation Index and Prognostic Nutritional Index in Primary Hyperparathyroidism - Yusuf Karadeniz; Melia Karakose (Medicina)
Background/Objectives: Primary hyperparathyroidism (PHPT) has been associated with systemic inflammation and metabolic disturbances. This study aimed to evaluate changes in the Systemic Immune-Inflammation Index (SII) and Prognostic Nutritional Index (PNI) following parathyroidectomy (PTX) in PHPT patients, and to assess their return toward healthy control values. Materials and Methods: This retrospective study was conducted between January 2010 and March 2022. It analyzed the demographic characteristics, clinical findings, and laboratory results of patients diagnosed with and operated for PHPT, with comparisons to healthy controls. Postoperative values were recorded at least six months after surgery. Bone mineral density was classified according to World Health Organization criteria, and nephrolithiasis was assessed with imaging. Results: After applying exclusion criteria, 415 PHPT patients and 410 controls were included. PHPT patients were older (p < 0.001) and had a higher proportion of females (p = 0.016). Compared to controls, they had lower phosphorus, albumin, high-density lipoprotein cholesterol, total cholesterol, hemoglobin, and PNI (p < 0.001 for all), while triglycerides, monocytes, platelets, CRP, and SII were higher (p < 0.05). Postoperatively, albumin, platelets, total cholesterol, and triglycerides increased (p < 0.001), while calcium, white blood cell count, neutrophils, lymphocytes, and CRP decreased (p < 0.05), approaching healthy control values. In age- and sex-matched comparisons (propensity score matching, n = 259 in each group), platelets (p = 0.002) and hemoglobin (p = 0.018) were found to be higher postoperatively. Conclusions: Preoperative SII and PNI levels were significantly altered in PHPT patients compared to healthy controls. Following PTX, both of these markers and other parameters showed significant improvements, reflecting positive changes in systemic inflammation and nutritional status.